The first-principles study of BC3 nanosheet as the delivery vehicle for 6-mercaptopurine drug. (16th February 2022) - Qin, Yong; Xu, Haiting; Zhou, Nan; Chen, Xuekun; Peng, Zhihua; Nie, Changming; Tan, Jie; Wu, Xijun
Abstract : In this study, the potential applications of perfect boron carbide (BC3 ) nanosheet and single-vacancy defect BC3 nanosheets (SVBC3 -B and SVBC3 -C), as the drug delivery vehicle for 6-mercaptopurine (6-MP), are investigated based on the calculation of the density functional theory (DFT). The interactions of the 6-MP drug with the BC3 nanosheet, SVBC3 -B and SVBC3 -C are simulated in the gas phase, water solvent and acidic solvent, respectively. The results demonstrated that the 6-MP drug tends to adsorb parallel on the surface of the BC3 nanosheet, and the adsorption energy on SVBC3 -B is the largest, followed by the perfect BC3 . The interactions between the 6-MP drug and the perfect BC3 nanosheet, SVBC3 -B and SVBC3 -C will be weakened in a water solvent. Furthermore, the interaction force between the 6-MP drug and the perfect BC3 nanosheet or SVBC3 -B nanosheet in an acidic solvent is more significant than that in a water solvent, which is not conducive to separating the 6-MP drug from the two kinds of BC3 nanosheets. But, the adsorption energy of the 6-MP drug on SVBC3 -C in the acidic solvent is much lesser than that in the water solvent, which indicates that the 6-MP drug can be easily separated from SVBC3 -C in the acidic environment. The PH value of cancer tissue is just acidic, which provides an ideal environment for separating 6-MP. Generally, the results confirmed the possibility of SVBC3 -C as a delivery vehicle for the 6-MP drug. GRAPHICAL ABSTRACT: UF0001